Documentos administrativos: Actas, oficios, solicitudes y memorando - Sanchez Garcia, Alonso (2018)
Through the development of this Learning Session it is intended to build in the student (a) the information necessary to understand, process and produce messages. The way in which students express themselves and understand the messages will be taken into account, if they are able to communicate by making it clear to others what they want to express and understand what others intend to communicate. Reading and writing will be encouraged for pleasure, to write administrative documents, to socialize their readings, to give them the opportunity to value what they learn with reading, organize what they have learned and arouse the curiosity of others to read and write texts. The motivating reading is through examples found in the Communication books delivered by the MINEDU, waiting for the objectives set.